Berry Raw Materials in Functional Soft Cheese Production - Borisova A.; Ruzyanova A.; Tyaglova A.; Polikarpova K. (Техника и технология пищевых производств)
Introduction. Healthy diet has been in the focus of scientific attention for many years. This issue is closely connected with the production of functional foods. Functional food products contain functional ingredients that are beneficial to living systems. The present research features functional soft cheese based on dried berries that are rich in vitamin C, which possesses antioxidant activity, reduces the risk of blood clots, and improves the immune system. Study objects and methods. An online survey was conducted to study the Russian cheese market. The experiments featured samples of sea-buckthorn, aronia, and rosehip berries and samples of milk whey obtained at different stages of cheese production. The sampels of the berries were analysed for physical and chemical properties, i.e. acidity, contents of dry substances, moisture, food fibers, vitamin C content, etc. Acidity of milk whey was evaluated in pH. Results and discussion. The market analysis revealed that Russian cheese market needs to be expanded. Potential customers would agree to purchase cheese with various berry additives. Almost 30% of respondents claimed that they would like to buy cheese with sea-buckthorn berries. We produced four samples of cheese with raw material that was rich in vitamin C. A panel of six potential customers evaluated the samples for sensory properties using a five-point scale, i.e. color, taste, aroma, consistency, and shape. The sea-buckthorn cheese received the highest score: 22.3 points out of 25. Conclusion. Powdered sea-buckthorn, aronia, and rosehip berries could be used to produce quality functional soft cheese. The research helped to define the optimal way of introducing berry additives into cheese products. Powdered berries were introduced while mixing curd, which helped to maintain whey acidity at the required level and improve the qualitaty of the final product. When the powdered berries were introduced into the milk before the enzyme, the consistency of the obtained cheese was unsatisfying: it broke down into curds, and its viscosity was low.